A comparative evaluation of leadership in business and leadership in the Church to discover principles of Christ-like leadership that would help leaders lead effectively in any environment. - Nel, Malan (University of Pretoria, 2013)
Dissertation (MA (Practical Theology))--University of Pretoria, 2008.